On the first power mean of L-functions with the weight of general Kloosterman sums - Zhang Wenpeng (International Journal of Mathematics and Mathematical Sciences)
The main purpose of this paper is using the estimates for character sums and the analytic method to study the first power mean of Dirichlet L-functions with the weight of general Kloosterman sums, and give an interesting asymptotic formula.